Pemeriksaan Laboratorium sebagai Indikator Sepsis dan Syok Septik - Purwanto, Diana S.; Astrawinata, Dalima A.W. (Jurnal Biomedik : JBM, 2019)
Abstract: The complexity of the pathogenesis and pathophysiology of sepsis involves almost all types of cells, tissues, and organ systems. Therefore, there are numbers of laboratory tests that can be used as biomarkers of sepsis and septic shock. Some widely used biomarkers are divided into groups of bacterial products, acute phase proteins, tissue hypoperfusion, coagulation mediators, cell surfaces, and cytokines.Keywords: sepsis, septic shock, biomarkersAbstrak: Kompleksnya patogenesis dan patofisiologi sepsis melibatkan hampir semua jenis sel, jaringan, dan sistem organ. Oleh karena itu, terdapat banyak parameter laboratorik yang dapat dijadikan biomarker sepsis dan syok septik. Berbagai biomarker yang banyak digunakan terbagi dalam kelompokan produk bakteri, protein fase akut, hipoperfusi jaringan, mediator koagulasi, permukaan sel, dan sitokin.Kata kunci: sepsis, syok septik, biomarker